(untitled) (New York, 2005)
The groundbreaking canopy-access and rain forest research at Lambir Hills National Park in Sarawak, Malaysia, has contributed an immense body of knowledge. Its major studies over more than a decade are synthesized here for the first time. The focus of this unique volume is on plant-animal interactions and some of the foundations that create and maintain tropical diversity, especially pollination and the phenomenon of the General Flowering. The work discussed has implications for tropical biology, ecology, and pollination studies. The power of the El Nino-Southern Oscillation events and drought, particularly in their effects on mutualisms, are discussed in detail.
Keywords: Rain forest ecology,Pollination; Malaysia,Sarawak,Malaysia,Sarawak